2022
DOI: 10.1111/sifp.12209
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enablers Influencing Women's Adoption and Continuation of Vaginally Inserted Contraceptive Methods: A Literature Review

Abstract: Most vaginally inserted methods have limited availability and use despite offering characteristics that align with many women's stated preferences (e.g., nonhormonal and/or on demand). The objective of this review was to identify enablers and barriers to women's adoption and continuation of vaginally inserted contraceptive methods in low-and middle-income countries (LMICs). We searched three databases (PubMed, Embase, and Web of Science) and  websites using keywords related to five vaginally inserted contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 204 publications
(954 reference statements)
0
3
0
Order By: Relevance
“…Male contraception and new non-hormonal products for women may fill this gap and allow greater control of reproduction. A new contraceptive product that is low-cost, easily accessible, user-controlled, non-invasive, reversible, safe, and unobtrusive during intercourse might be popular among women who presently do not consistently use effective contraception methods due to their high cost, limited access and undesirable side effects [ 2 , 3 ]. A promising new contraceptive candidate is the Human Contraception Antibody (HCA), an antisperm antibody currently in clinical development as a topical non-hormonal contraceptive for women [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Male contraception and new non-hormonal products for women may fill this gap and allow greater control of reproduction. A new contraceptive product that is low-cost, easily accessible, user-controlled, non-invasive, reversible, safe, and unobtrusive during intercourse might be popular among women who presently do not consistently use effective contraception methods due to their high cost, limited access and undesirable side effects [ 2 , 3 ]. A promising new contraceptive candidate is the Human Contraception Antibody (HCA), an antisperm antibody currently in clinical development as a topical non-hormonal contraceptive for women [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent literature review assessing barriers and enablers to women's uptake and use of vaginal contraception suggested that concerns about vaginal insertion as a disincentive to a product's The star (*) denotes a probability value < 0.05 using a χ 2 test of association. demand are likely overestimated (23). Indeed, numerous studies suggest that intravaginal practices are common and are engaged in for cleaning purposes, sexual pleasure, and fertility control (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Across 68 studies, including both clinical trial and observational designs of different types of vaginal rings, most women rated their IVR experience as highly acceptable, and insertion and removal as easy ( 18 , 22 ). Indeed, a recent literature review assessing barriers and enablers to women's uptake and use of vaginal contraception suggested that concerns about vaginal insertion as a disincentive to a product's demand are likely overestimated ( 23 ). Indeed, numerous studies suggest that intravaginal practices are common and are engaged in for cleaning purposes, sexual pleasure, and fertility control ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%